British or American English? A Survey on Speech - Svanhildur Sif Halldórsdóttir 1985- (2014)
The aim of this survey is to determine whether Icelanders use more British English or American English in their speech. British English is taught in most compulsory and secondary schools in Iceland but most English input comes from the United States. The research shows that males are more likely to use British English in their speech than females. They are also better at determining whether a sentence is written in British English or American English. The research indicates that older participants are better at determining whether a sentence is written in British or American English than younger participants. Older participants also use more British English in their speech than younger participants. Participants with a university education are more likely to use British English in their speech, and are better at determining whether a sentence is written in British English or American English, than participants who only had a secondary education or compulsory education. Unfortunately the participants do not represent the entire country as the majority are females and university-educated, so further studies in this area are needed.